Теория и практика изучения этнической идентичности в социологии и социальной психологии - Козлова, Елена Аркадьевна (Національний технічний університет "Харківський політехнічний інститут", 2018)
В настоящий момент проблема изучения этнической идентичности в современной Украине чрезвычайно актуальна. Активное содействие росту положительной этнической идентичности должно получить статус приоритетных в социальной политике нашего государства. Автором рассмотрены ряд теоретических и практических аспектов изучения этнической идентичности и особенностей ее формирования в украинском обществе. Проанализированы этапы формирования этнической идентичности а также ее типы. Использованы материалы собственного исследования, в ходе которого были проанализированы особенности формирования этнической идентичности у студентов-социологов НТУ «ХПИ». Исследование показало, что для большинства студентов (около 75%) характерна моноэтническая идентичность, они стойко идентифицируют себя с украинским этносом. Также, к важнейшим агентам социализации, которые повлияли на становлении их этнической идентичности, студенты относят семью, систему образования, школьных учителей, СМИ. Тестирование, проводимое с помощью опросника Г. В. Солдатовой, показывает, что около 65% студентов имеют позитивную этническую идентичность (норму), реже встречается этническая индифферентность и этонигилизм.

Currently the problem of research ethnic identity in the modern Ukraine is highly relevant. Active promoting the growth of positive ethnic identity should receive the status of a priority objective in the social policy of the state. The author reviewed a number of theoretical and practical aspects of research ethnic identity and the factors of its formation in Ukrainian society. Ethnic identity is the person perception of belonging to a specific ethnic communityand separation from other ethnic groups. Ethnicity is determined by a number of objective indicators: the ethnicity of the parents, place of birth, language, culture. The following components can be distinguished in its structure: cognitive (knowledge, conception about the group to which the person belongs and self-awareness as a member); affective (feeling of belonging to a group, quality evaluation of it, respect to membership in it) and behavioral (actions or rejection of it by an individual in accordance with his type of ethnic identity). In the process of its formation, ethnic identity goes through a series of stages correlated with the stages of a child’s mental growth. At the same time ethnic self-conscience formed later than other forms of self-conscience. Study on ethnic identity makes it plausible that in the process of its formation depends on combination of various causes and conditions, several types can be formed, differing in the features and characteristics. These types include: monoethnic identity, monoethnic identity with a foreign ethnic group, biethnic identity and marginal identity. The materials of own research were used, during which the factors in the creation of an ethnic identity among sociological students of NTU “KPI” were analyzed. Research showed that the majority of students (about 75%) are characterized by a mono-ethnic identity. They definitely identify themselves with the Ukrainian ethnos. Also, to the most important agents of socialization, which influenced the formation of their ethnic identity, the students include the family, the education system, school teachers, the media. Testing conducted using the questionnaire G.V. Soldatova shows that about 65% of students have a positive ethnic identity (norm). Ethnic indifference and ethnicity are less common. In conclusion, the point of the current stage ethnic identity formation in Ukraine determined by the need to find an optimal and acceptable for the majority of the population model of ethnic identity, which would harmoniously combine national and universal human values.
Theory and practice of research ethnic identity in sociology and social psychology
Keywords: этнос; этническая идентичность; Я-концепция; типы этнической идентичности; ethnos; ethnic identity; self-concept; types of ethnic identity